Expectations of furniture buyers at the Malaysian International Furniture Fair 2016 - Zariffuddin, Ahmad Nashriq (2018)
This research was done during the Malaysian International Furniture Fair 2016 at the Kuala Lumpur Convention Center (KLCC).The objective of this research was to provide basic information on the various aspects of consumer behavior to identify such as the kinds of furniture buying characteristics, the type of materials other than wood and wood species preferred that are widely used in furniture at the Malaysian International Furniture Fair. In addition to that, the research also aimed to identify the factors that influence buyers to purchase wood-based furniture and initiative to improve marketability of Malaysian Furniture. The research involved 150 respondents, where the majority came from Malaysia, Singapore, United States, United Kingdom, United Arab Emirates and a few European Countries. The highest average respondents spent a budget of RM10,000, and white being the most favored color for their furniture. The respondents also preferred classic furniture and modern designs. Leather was the main choice for the type of textile they preferred on their furniture. ISO-9001 was the most sought after quality certification amongst the respondents that determines the quality of the furniture. Transparent coating was also the most preferred coating that was desired amongst consumers. Respondents also desired solid wood as their choice of wooden furniture & chose rattan for non-wooden furniture. For the types of wood that most preferred, research shows that local species mostly rubber wood while imported species were mainly made of oak. Factors that persuaded consumers in buying wooden furniture was the quality and design. Aesthetic appeal, availability, high demand and environmental friendly are all factors that influence the species of wood being chosen. Among the initiatives taken to raise marketability Malaysian Furniture is to attend furniture fair. The conclusion of this study shows that Malaysia has a huge potential to become a recognized furniture-driven export country in the world.